Earthquake nucleation and fault slip complexity in the lower crust of central Alaska - Tape, C; Holtkamp, S; Silwal, V; Hawthorne, J; Kaneko, Y; Ampuero, JP; Ji, C; Ruppert, N; Smith, K; West, ME (Springer Nature, 2018)
Earthquakes start under conditions that are largely unknown. In laboratory analogue experiments and continuum models, earthquakes transition from slow-slipping, growing nucleation to fast-slipping rupture. In nature, earthquakes generally start abruptly, with no evidence for a nucleation process. Here we report evidence from a strike-slip fault zone in central Alaska of extended earthquake nucleation and of very-low-frequency earthquakes (VLFEs), a phenomenon previously reported only in subduction zone environments. In 2016, a VLFE transitioned into an earthquake of magnitude 3.7 and was preceded by a 12-hour-long accelerating foreshock sequence. Benefiting from 12 seismic stations deployed within 30 km of the epicentre, we identify coincident radiation of distinct high-frequency and low-frequency waves during 22 s of nucleation. The power-law temporal growth of the nucleation signal is quantitatively predicted by a model in which high-frequency waves are radiated from the vicinity of an expanding slow slip front. The observations reveal the continuity and complexity of slip processes near the bottom of the seismogenic zone of a strike-slip fault system in central Alaska.